2022
DOI: 10.3390/su14137898
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and Its Impact on Language Achievement: Sustainable Development of Ethnic Minority Students’ Second Language Learning

Abstract: This study examined the English learning motivation of Chinese ethnic university students. A sample of 776 undergraduates from three representative ethnic universities participated in this research. The findings indicated four types of English learning motivation: intrinsic interest, learning situation, personal development, and international communication. There were statistically significant differences between ethnic minority and Han students, and between male and female students. Moreover, the intrinsic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 75 publications
(103 reference statements)
3
16
0
Order By: Relevance
“…Moreover, the ADIDAS model was designed according to Piaget’s cognitive constructivist theory principles and modern instructional models, which were created during COVID-19, that ensured effective learning and enhanced mental load distribution during SDL. Accordingly, the students had low cognitive load levels while learning within the ADIDAS model [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the ADIDAS model was designed according to Piaget’s cognitive constructivist theory principles and modern instructional models, which were created during COVID-19, that ensured effective learning and enhanced mental load distribution during SDL. Accordingly, the students had low cognitive load levels while learning within the ADIDAS model [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…To develop a draft of the ADIDAS model and answer the first research question, the literature review related to digital learning, especially amid COVID-19, instructional design models, and cognitive load as well as learning theories from various databases that we have reviewed and analysed (see Appendix A ). After screening the literature, we focused our analysis on the ADDIE model [ 43 ], interaction analysis model (IAM) [ 44 ], and model of self-regulated learning (SRL) [ 45 ] to develop the first draft of the ADIDAS model.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, second language learning motivation is an important concept that cannot be ignored in second language learning [29]. Generally, second language learning motivation can be categorized into three aspects [30,31]. The first one is socio-educationalbased theory, which mainly includes integrative and instrumental motivation.…”
Section: Motivation Compositionmentioning
confidence: 99%
“…A recent study indicated that intrinsic interest motivation had a direct positive impact on science achievement [56]. Besides, students who displayed more interest in learning were more likely to have higher academic achievement [30,57]. In the Asian context, intrinsic interest has been recognized as an influential factor in enhancing lifelong learning for students [58].…”
Section: Motivation and Academic Achievementmentioning
confidence: 99%
“…Although many scholars have done a great job in exploring English language learners' motivation (Ali, 2022;Jiao et al, 2022;Kühl and Wohninsland, 2022), there is a paucity of research into its role in the graduate students majoring in translation. China established the MTI Program to cultivate translation talents in China in 2007.…”
Section: Introductionmentioning
confidence: 99%